Evaluation of charged-particle induced nuclear reactions cross-sections for the production of non-standard medical radionuclides 55Co, 61Cu and 186Re / Samer Kamal Issa Ali - Samer Kamal , Issa Ali (2019)
Radioisotopes that emit positrons and beta particles show great potential to be used as an active material in diagnostic and therapeutic radiopharmaceuticals, respectively. The radionuclides 55Co, 186Re and 61Cu can be produced via several pathways, however charged-particle induced nuclear reactions show promising towards no carrier added (NCA) production. Many experiments for the production cross-sections of the aforementioned radionuclides were conducted around the world in the last few decades, and they are available in various platforms such as journals, database etc. The EXFOR library, which is maintained by the International Atoms Energy Agency (IAEA), contains an extensive compilation of experimental nuclear reaction cross-sections reported by various authors throughout the world. Nuclear reaction cross-sections play an important role to determine the possibility of producing a radionuclide in pure form or in NCA form. But production cross-sections for a particular radionuclide measured by different authors and/or in laboratories mostly show considerable discrepancies. However, it is possible to overcome the existing discrepancies among the data sets, if the experimental data could be evaluated precisely. Specifically, a more accurate form of nuclear reaction cross-sections can be obtained by evaluating reported cross-sections considering all relevant parameters with respect to the updated ones, i.e., latest agreed values of standards. In this work, cross-sections for 55Co, 61Cu and 186Re radionuclides measured via light-ion-induced nuclear reactions those available in the EXFOR library are evaluated in low energy range. An effective evaluation technique such as Simultaneous Evaluation on KALMAN (SOK) code are used in this evaluation. SOK code mainly used KALMAN filter combined with least squared method to give values close to the real cross-sections for the reactions of interest, and also to reduce the reported experimental errors in a mathematically correct way. KALMAN filter combined with least square concept was used to obtain the evaluated data together with covariances matrices, and finally obtained one fitted curve following the concept of spline fitting technique. The evaluated cross-sections obtained via SOK code are compared with the calculated cross-sections obtained via some established nuclear reaction model codes such as TALYS (Developed by NRG in Petten, the Netherlands, and CEA in Bruyères-le-Châtel, France) and EMPIRE (Developed by Brookhaven National Lab, USA and IAEA). Our evaluated cross-sections show partial agreement with the calculated data by Talys and Empire code.